Evaluating software inspection cognition levels using Blooms Taxonomy - McMeekin, David; von Konsky, Brian; Chang, Elizabeth; Cooper, David (IEEE Computer Society, 2009)
This paper reports on results from a pilot study that used Bloom's Taxonomy to observe cognition levels during software inspections conducted by undergraduate computer science and software engineering students. Cognition levels associated with three different code inspection techniques were investigated. These were the Ad hoc, Abstraction Driven, and Checklist-based reading strategies. Higher cognition levels were observed when using inspection techniques that utilise a more structured reading process. This result highlights the importance of introducing novice programmers to structured code reading strategies. Findings suggest that teaching different software inspection techniques throughout software courses, beginning with structured techniques, is an excellent way to build a student's critical software reading and analysis skills.